Targeting of CXCR4 by the Naturally Occurring CXCR4 Antagonist EPI-X4 in Waldenström’s Macroglobulinemia - Kaiser, Lisa Marie (Cancers (Basel), 2021)
SIMPLE SUMMARY: Waldenström’s Macroglobulinemia is a B-cell lymphoma, for which no curative established treatment exists. One of the drivers of tumor growth in this disease are genetic alterations of the gene CXCR4, which can be found in up to 40% of patients with this disease. Patients with CXCR4 mutations typically have a more aggressive disease. In this article we provide evidence that a naturally occurring peptide, called EPIX4 and its optimized derivatives bind to CXCR4 on Waldenström’s macroglobulinemia cells and are able to impair growth of these lymphoma cells in mice. These data highlight that there are natural mechanisms which counteract CXCR4 driven lymphoma growth. In addition, they underline that optimizing naturally occurring CXCR4 antagonists can potentially lead to the development of novel therapies in Waldenström’s macroglobulinemia, particular in patients with CXCR4 alterations affected by a more aggressive course of disease. ABSTRACT: CXCR4 expression and downstream signaling have been identified as key factors in malignant hematopoiesis. Thus, up to 40% of all patients with Waldenström’s macroglobulinemia (WM) carry an activating mutation of CXCR4 that leads to a more aggressive clinical course and inferior outcome upon treatment with the Bruton’s tyrosine kinase inhibitor ibrutinib. Nevertheless, little is known about physiological mechanisms counteracting CXCR4 signaling in hematopoietic neoplasms. Recently, the endogenous human peptide EPI-X4 was identified as a natural CXCR4 antagonist that effectively blocks CXCL12-mediated receptor internalization and suppresses the migration and invasion of cancer cells towards a CXCL12 gradient. Here, we demonstrate that EPI-X4 efficiently binds to CXCR4 of WM cells and decreases their migration towards CXCL12. The CXCR4 inhibitory activity of EPI-X4 is accompanied by reduced expression of genes involved in MAPK signaling and energy metabolism. Notably, the anti-WM activity of EPI-X4 could be further augmented by the rational design of EPI-X4 derivatives showing higher binding affinity to CXCR4. In summary, these data demonstrate that a naturally occurring anti-CXCR4 peptide is able to interfere with WM cell behaviour, and that optimized derivatives of EPI-X4 may represent a promising approach in suppressing growth promoting CXCR4 signaling in WM.